A Genetic Algorithm Based Minimal Maximal Load Tree Routing Algorithm in Wireless Sensor Networks. (8th November 2015) - Huang, Zhi
Abstract : The key issue of static routing algorithms is how to construct an energy efficient routing tree that is utilized during the whole network duration in order to extend network lifetime. In this paper, we have illuminated that, in applications that define network lifetime as the time when the first sensor dies, the optimal routing tree should be the routing tree with minimal maximal load of all sensors and named such trees the Minimal Maximal Load Tree (MMLT). Since the procedure of constructing a routing tree is complex and the number of possible routing trees in a network is very huge, we have proposed a genetic algorithm (GA) based algorithm to obtain approximate Minimal Maximal Load Tree (MMLT). Each individual corresponds to a routing tree, and the fitness function is defined as the maximal load of all sensors in accordance with the routing tree that the individual corresponds to. Thus, approximate MMLT is obtained and network lifetime is extended. Simulation results show that our proposed algorithm notably extends network lifetime.